PENGARUH TRADISI TABOB TERHADAP PENYU BELIMBING DI KEPULAUAN KEI, MALUKU TENGGARA - Retawimbi, Aditano Yani (Sabda: Jurnal Kajian Kebudayaan, 2011)
One of the traditions of the society of Nu Fit The Kei, Southeast Maluku, which is Tabob to perform a ritual to hunt and consume the meat of the species of leatherbacks Dermochelys coriacea (leatherback turtle). More recently, the tradition of tabob examined became one of the causes of the declining population of leatherbacks, so this turtle species need protection to keep it from extinction. In this article in question is, does the ritual of tabob significantly affect a decrease in the number of population of leatherbacks.